Adaptive Building Blocks Consisting of Rigid Triangular Core and Flexible Alkoxy Chains for Self-Assembly at Liquid/Solid Interfaces - Tobe, Yoshito; Tahara, Kazukuni; De Feyter, Steven (Bulletin of the Chemical Society of Japan, 2016)
Supramolecular self-assembly in two-dimensional (2D) spaces on solid surfaces is the subject of intense current interest because of perspectives for various applications in nanoscience and nanotechnology. At the liquid/graphite interface, we found by means of scanning tunneling microscopy molecules with a rigid triangular core, a twelve-membered phenylene-ethynylene macrocycle called dehydrobenzo[12]annulene (DBA), substituted by six flexible alkoxy chains self-assembled to form hexagonal porous 2D molecular networks via van der Waals interactions between interdigitated alkyl chains as the directional intermolecular linkages. Factors that affect the formation of the porous 2D molecular networks including alkyl chain length, solvent, solute concentration, and temperature were elucidated through a systematic study. Because DBA molecules are versatile for chemical modification, they turned out to be highly adaptive for on-surface supramolecular chemistry with respect to (i) pore size control by changing the chain length, (ii) study of parity effect due to even or odd number chains, (iii) generation of supramolecular chirality on surfaces by introducing stereocenters, (iv) chemical modification of the pore interior for selective co-adsorption of guest molecules by introducing functional groups. Additionally, formation of superlattice structures on surfaces was incidentally observed by mixing DBAs of different alkoxy chain parity or by addition of guest molecules via an induced-fit mechanism. These results made significant contribution to advancement of supramolecular chemistry in 2D space.